Incorporation of indium oxide into the growth of multiwall carbon nanostructures via a solid–liquid–solid mechanism - Supangat, A.; Zulfiqar, H.; Kamarundzaman, A. (Elsevier, 2013)
In this study, the diffusion and incorporation of indium oxide nanostructure into the growth of multiwall carbon nanostructure (MWCN) is reported. MWCN was successfully grown on iron coated indium tin oxide (ITO) substrate via the chemical vapour deposition (CVD) of acetylene (C2H2). Indium oxide nanostructure that originated from ITO substrate is incorporated into the MWCN growth via a solid–liquid–solid mechanism. Under the present working temperature of 400 °C, indium oxide has been potentially diffused and incorporated into the MWCN growth which brings to the perception of carbon growth on particular substrate. The type of transparent conducting oxide substrate used in this study has much contribution to the MWCN growth.